Cooperative Catalysis of Nickel and Nickel Oxide for Efficient Reduction of CO2 to CH4. Issue 4 (23rd January 2019) - Bi, Qingyuan; Huang, Xieyi; Yin, Guoheng; Chen, Tianyuan; Du, Xianlong; Cai, Jun; Xu, Jing; Liu, Zhi; Han, Yifan; Huang, Fuqiang
Abstract: The use of CO2 to produce value‐added energy chemicals is a promising means for renewable CO2 transformation in low‐carbon energy system, and CO2 methanation has attracted ever‐increasing interest. Herein, we report that the Ni/MCM‐41 catalyst with prominent cooperative effect of Ni and NiO is efficient for CH4 generation with CO2 conversion of 73.2 % and CH4 selectivity of 91.6 % at 400 °C and high gas hourly space velocity (GHSV) of 90000 mL gcat −1 h −1 . Combined methodologies of in situ X‐ray diffraction, diffuse reflectance infrared Fourier transform spectroscopy, and ambient‐pressure X‐ray photoelectron spectroscopy reflect the structural evolvements of Ni/MCM‐41 catalyst, the presence of carbonyl intermediates, the co‐existence of metallic and oxidized Ni species with sufficient molar ratio of Ni 0 /Ni 2+ under working conditions. H2 and CO2 molecules are preferentially adsorbed and chemically activated over Ni 0 and Ni 2+ species, respectively. The possible four‐step reaction mechanism involved carbonyl pathway and the cleavage of C=O bond from CO2 as the rate‐determining step over the engineered Ni/MCM‐41 catalyst was demonstrated. Abstract : Cooperative effect is essential to metal and metal oxide catalysis for CO2 transformation in low‐carbon energy system. Catalytic reduction of CO2 to CH4 at high gas hourly space velocity is significantly boosted by the cooperative Ni‐NiO catalyst, presenting an efficient and reliable route to CH4 generation.